Der Mann, das Mädchen und der Dichter: Zur Frage der Absicht dreier Personen: Eine Verführungsgeschichte (Archil. 196a W2) - Mayer, Péter (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
No abstract is available for this article, published in Acta Classica Universitatis Scientiarum Debreceniensis, Issue XLII, 2006. At the time of publication, abstracts were not required from the authors. Please consult the full text for further details.